2002
DOI: 10.1097/00007890-200210270-00027
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of secondary myelodysplastic syndrome after heart transplantation with chemotherapy and nonmyeloablative stem-cell transplantation1

Abstract: Allogeneic blood stem-cell transplantation using minimal conditioning is a new, promising treatment option for patients with hematologic malignancies after solid-organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…Over the last 20 years, several case reports have detailed encouraging results of alloSCT in solid organ transplant recipients . In a summary of published cases by Chiang and Lazarus , 8/10 recipients of alloSCT after SOT were alive at the last follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 20 years, several case reports have detailed encouraging results of alloSCT in solid organ transplant recipients . In a summary of published cases by Chiang and Lazarus , 8/10 recipients of alloSCT after SOT were alive at the last follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Two patients survived at a follow-up of 7-22 months after receiving myeloablative conditioning regimen. Kobbe et al 18 reported successful use of non-myeloablative conditioning regimen followed by matching-related HSCT for a patient with MDS following heart transplantation. The use of allogeneic HSCT for PTLD has not been previously described…”
Section: Discussionmentioning
confidence: 99%
“…He is now more than 4.5 yr after HCT from an HLA‐matched, ABO incompatible brother and has remained in complete remission of his leukemia. Another 60‐yr‐old man had developed MDS‐refractory anemia with excess blasts 10 yr after orthotopic heart transplantation (31). He received remission induction with chemotherapy followed by HCT from an HLA‐matched ABO incompatible sister.…”
Section: Hematological Malignanciesmentioning
confidence: 99%